2021
DOI: 10.1177/15598276211018159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Whole-Foods, Plant-Based Nutrition Intervention on Patients Living with Chronic Disease in an Underserved Community

Abstract: The current study evaluated the impact of a whole-foods, plant-based nutrition intervention on metabolic markers of patients with chronic disease in an underserved community setting. A retrospective analysis of metabolic biomarkers preintervention and postintervention was conducted on 31 patients with metabolic disease who attended an Eating for Life group visit series. Significant decreases were found for body mass index (BMI; −0.66 [−0.91 to −0.40] kg/m2), systolic blood pressure (−12 [−19 to −5] mm Hg), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In some small studies, nutrition education has been shown to have an impact on clinically important biomarkers. For example, in a study of 31 patients with chronic disease, an intensive nutrition education model with group and individual visits emphasizing whole, plant-based foods, significant improvements were shown in BMI, blood pressure, and cholesterol levels after 8 weeks [ 24 ]. However, in that study, as in many similar studies, participants were not randomized (all received the intervention).…”
Section: Discussionmentioning
confidence: 99%
“…In some small studies, nutrition education has been shown to have an impact on clinically important biomarkers. For example, in a study of 31 patients with chronic disease, an intensive nutrition education model with group and individual visits emphasizing whole, plant-based foods, significant improvements were shown in BMI, blood pressure, and cholesterol levels after 8 weeks [ 24 ]. However, in that study, as in many similar studies, participants were not randomized (all received the intervention).…”
Section: Discussionmentioning
confidence: 99%
“…• A whole-food, plant-predominant eating pattern (6,7) • Promotes leaner body mass, which is desirable for improved athletic performance • Has a multitude of benefits including helping to maintain weight, increase energy, promote better sleep, and improve mood (8) Sleep • Getting restorative sleep (for most people, between 7 and 9 h of sleep a day)…”
Section: Nutritionmentioning
confidence: 99%